2012
DOI: 10.1177/0273475312450385
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Influence of Professor Characteristics on Student Satisfaction and Dissatisfaction

Abstract: This research uses the Kano model of satisfaction to investigate professor characteristics that create student satisfaction as well as those attributes that can cause their dissatisfaction. Kano questionnaires were handed out to 104 undergraduate students at a university in the Southwest and to 147 undergraduate students at a university in the Midwest of the USA. The two resulting Kano maps show the same delighting attributes while other satisfaction attributes are also similar.The findings reveal the importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 109 publications
(188 reference statements)
1
30
0
8
Order By: Relevance
“…Adds spice to the lecture class experience, but is not the main course. Students are delighted by variety during the lecture class (Gruber et al, 2012). Instructor-created videos are a good source of variety.…”
Section: Video Technology Enables Doing Something New or Atmentioning
confidence: 99%
“…Adds spice to the lecture class experience, but is not the main course. Students are delighted by variety during the lecture class (Gruber et al, 2012). Instructor-created videos are a good source of variety.…”
Section: Video Technology Enables Doing Something New or Atmentioning
confidence: 99%
“…As partners in higher education, the students hope to have a satisfying experience in the classroom with a valuable learning experience. So that the management in the classroom into something valuable for students, thus, faculty characteristics tend to be the main determinant of student satisfaction in higher education [38].…”
Section: Advances In Economics Business and Management Research Volmentioning
confidence: 99%
“…Student loyalty variable adopted from [10], [14], [16], [21], [51], [52]. The image of the college adopted from [53], adopted from the student satisfaction [38], [51] and the Trust adopted from [18].…”
Section: Advances In Economics Business and Management Research Volmentioning
confidence: 99%
“…For example, past research on traditional SETs has identified biases based on gender [3][4][5][6][7][8], race [6,9], attractiveness [10], and age [7,11,12]. Many have also criticized traditional SETs as invalid measures of teaching quality and student learning [3,7,[12][13][14][15][16][17] and warned university administrators against using them for hiring and promotion decisions [18]. In light of these issues, there have been intensifying claims that SETs harm both students and faculty [19] and public calls to stop relying on them for evaluating teaching [20,21].…”
Section: Introductionmentioning
confidence: 99%